LDL Receptor Pathway Regulation by miR-224 and miR-520d - Salerno, Alessandro G.; van Solingen, Coen; Scotti, Elena; Wanschel, Amarylis C. B. A.; Afonso, Milessa S.; Oldebeken, Scott R.; Spiro, Westley; Tontonoz, Peter; Rayner, Katey J.; Moore, Kathryn J. (Frontiers in Cardiovascular Medicine, 2020)
MicroRNAs (miRNA) have emerged as important post-transcriptional regulators of metabolic pathways that contribute to cellular and systemic lipoprotein homeostasis. Here we identify two conserved miRNAs, miR-224 and miR-520d, which target gene networks regulating hepatic expression of the low-density lipoprotein receptor (LDLR) and LDL clearance. In silico prediction of miR-224 and miR-520d target gene networks showed that they each repress multiple genes impacting the expression of the LDLR, including the chaperone molecules PCSK9 and IDOL that limit LDLR expression at the cell surface, and the rate-limiting enzyme for cholesterol synthesis HMGCR, which is the target of LDL-lowering statin drugs. Using gain- and loss-of-function studies, we tested the role of miR-224 and miR-520d in the regulation of those predicted targets and their impact on LDLR expression. We show that overexpression of miR-224 or miR-520d dose-dependently reduced the activity of PCSK9, IDOL and HMGCR 3’-UTR-luciferase reporter constructs, and this repression was abrogated by mutation of the putative miR-224 or miR-520d response elements in the PCSK9, IDOL and HMGCR 3’-UTRs. Compared to a control miRNA, overexpression of miR-224 or miR-520d in hepatocytes inhibited PCSK9, IDOL, and HMGCR mRNA and protein levels, and decreased PCSK9 secretion. Furthermore, miR-224 and miR-520d repression of PCSK9, IDOL, and HMGCR was associated with an increase in LDLR protein levels and cell surface expression, as well as enhanced LDL binding. Notably, the effects of miR-224 and miR-520d were additive to the effects of statins in upregulating LDLR expression. Finally, we show that overexpression of miR-224 in the livers of Ldlr+/- mice using lipid nanoparticle mediated delivery resulted in a 15% decrease in plasma levels of LDL cholesterol, compared to a control miRNA. Together, these findings identify roles for miR-224 and miR-520d in the post-transcriptional control of LDLR expression and function.